CAD/CAM, Robotics and Factories of the Future Proceedings of the 28th International Conference on CARs & FoF 2016 - Mandal, Dipak Kumar; Syan, Chanan Singh (Lecture Notes in Mechanical Engineering,, 2016)
This volume is based on the proceedings of the 28th International Conference on CAD/CAM, Robotics and Factories of the Future. This book specially focuses on the positive changes made in the field of robotics, CAD/CAM and future outlook for emerging manufacturing units. Some of the important topics discussed in the conference are product development and sustainability, modeling and simulation, automation, robotics and handling systems, supply chain management and logistics, advanced manufacturing processes, human aspects in engineering activities, emerging scenarios in engineering education and training. The contents of this set of proceedings will prove useful to both researchers and practitioners.